The Influence of Corporate Governance Mechanism to Abnormal Return (Empirical study on companies listed on the Stock Exchange) - Cynthia Jayanti; Erwin Saraswati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims at examining the influence of a corporate governance mechanism which consists of transparency, fairness, accountability, and responsibility to the market reaction that is proxied by abnormal return. This study applies variable control on unexpected earnings and total cash flow. Population in this study is a non-financial sector companies listed on the Jakarta Stock Exchange in 2010. The selection of samples applies purposive sampling method and sample obtained, is 104 go public companies. This study uses secondary data that is the company's annual report. The results of this study show that the implementation of corporate governance has a significant influence to abnormal returns. This study also presents the fact that variable control total cash flow gives significant influence to abnormal returns. However, this study fails to show that the variable control on unexpected earnings has a significant influence to abnormal returns. Keyword: Corporate Governance, Abnormal Return, Unexpected Earnings, Total cash Flows